Achieving ultra-large elastic strains in Nb thin films on NiTi phase-transforming substrate by the principle of lattice strain matching. (1st January 2021) - Motazedian, Fakhrodin; Zhang, Junsong; Wu, Zhigang; Jiang, Daqiang; Sarkar, Satyajit; Martyniuk, Mariusz; Yan, Cheng; Liu, Yinong; Yang, Hong
Abstract: Two-dimensional nanomaterials are able to sustain ultra-large elastic strains, which in turn hold potential to alter the many functional properties. However, to achieve such large elastic strains in macro-forms suitable for applications has been a challenge. This paper reports an innovative approach to overcome this challenge by using a martensitic transforming substrate to induce ultra-large elastic lattice strains in metallic thin films deposited on it, as demonstrated in a Nb film-on-NiTi substrate system. This design is based on a novel concept of "lattice strain matching" between the uniform elastic lattice strain of the Nb film and the uniform crystallographic lattice strain of the martensitic transformation of the NiTi substrate. By this principle, the Nb film was able to exhibit reversible elastic lattice strains between −3.66% in compression and+3.74% in tension, for a total elastic strain span of +7.40% (the maximum in one loading deformation) by mechanical deformation of the substrate. These elastic lattice strains are 10–20 times of what are possible for bulk Nb or metallic thin films on conventional substrates. The findings of this work offer a unique opportunity to use ultra-large elastic strains as a means to engineer and improve functional properties of thin film materials. Graphical abstract: Unlabelled Image Highlights: Ultra-large elastic lattice strain of 6.88% was achieved in a Nb thin film deposited on a NiTi substrate It is enabled by "lattice strain matching" between elastic strain of Nb and transformation crystallographic strain of NiTi Such large elastic lattice strains enables design of functional materials by the principle of "elastic strain engineering" A unique XRD technique is developed to measure lattice strains in textured thin films